ADMINISTRATIVE INFORMATION SYSTEM DESIGN IN CASH SALES PT. ABC - Yudhi Destri Young; Yudi Irawan Chandra, SKOM., MMSI Yudi Irawan Chandra, SKOM., MMSI (Jurnal Sistem Informasi, 2007)
Information System of cash sales administration is an information system intendedfor the company as a tool to facilitate the handling of cash sales in a procedure whichis managed by the sales manual. This information system should be able to producemonthly reports of sales reports. Application administration is a real form of cashsales from cash sales administrative information system using computerizedtechnology.